Isotonic muscle function is selectively reduced after muscle damage induced by isometric exercise at a long muscle length - Philippou, A.a b , Bogdanis, G.C.a , Maridaki, M.a (Isokinetics and Exercise Science, 2007)
This study investigated the hypothesis that isotonic muscle performance following mild muscle damage would be disproportionately affected when measured at different parts of the range of motion. Seven male volunteers performed 50 maximal isometric contractions with the elbow flexors at a lengthened position. Maximal isotonic performance was measured before and for four days post-exercise at two parts of the range of motion of elbow flexion, including mainly the descending (L) or the ascending limb (S) of the angle-force curve. On day 1 post-exercise, muscle damage was evidenced by a decrease in peak isometric force (-20.3 ± 2.7%, p<0.01), a shift in optimum angle for force generation towards a greater elbow angle (by 0.12 ± 0.03 rad, p<0.05), and an increase in serum creatine kinase activity and muscle soreness (P<0.01). Isotonic performance indices were decreased only in the S condition (p<0.01). Shift in optimum angle and isotonic performance indices recovered on day 2. The disproportionate decrease in isotonic performance in the S condition may be explained by the shift of the optimum angle towards a longer muscle length, which would benefit force generation at elbow angles beyond the optimum angle but impair force at the more acute elbow angles. © 2007 - IOS Press and the authors. All rights reserved.